Resistance status and physiological responses of Dactyloctenium aegyptium to diuron herbicide in pineapple plantation - RESTI PUSPA KARTIKA SARI; NANIK SRIYANI; YUSNITA YUSNITA; HIDAYAT PUJISISWANTO (Jurnal Natural, 2022)
Diuron herbicide has been used in the pineapple plantation in Lampung, Indonesia, for more than 35 years. It has been realized that the use of herbicides with the same mode of action intensively can speed up the evolution of resistant weeds over a long period of time. This study aimed to determine whether Dactyloctenium aegyptium from pineapple plantation has evolved resistance to diuron and to examine whether the resistance correlates with the weed physiological activities. The study was conducted at the University of Lampung, from September 2018 to March 2019. The study consisted of two stages, i.e. Stage 1: Weed resistance test and Stage 2: Physiological activity test on resistant weed. The study used a split-plot design. The main plot was the origins of weeds (exposed and unexposed to diuron) and thhe supplots was the diuron dose. The result showed that D. aegyptium exposed has high-level resistance to diuron. The physiological activities of D. aegyptium which has a high level of diuron resistance exhibited higher carbon assimilation, stomatal conductance, and transpiration rates than the sensitive D. aegyptium.